A Qualitative Inquiry Into the Experiences of High-Potential Hispanic English Language Learners in Midwestern Schools. (August 2013) - Pereira, Nielsen; Gentry, Marcia
The underrepresentation of English language learners (ELLs) in gifted programs remains a severe and pervasive problem; however, few studies exist concerning the educational experiences of high-potential ELLs. This study focused on Hispanic ELLs in Grades 2 through 6 from four Midwestern schools. In all, 22 students, 20 parents, and 22 teachers were interviewed to gain a better understanding of the students' schooling experiences. Phenomenology and grounded theory provided theoretical frameworks. Students revealed that they enjoyed school, had positive interactions with peers and teachers, and were committed to doing well in school. Results of this study also revealed that the participants were well integrated in school. This study adds to the limited research concerning high-potential Hispanic ELLs and provides insights into these students' educational experiences, highlighting the need to focus on their strengths rather than on their deficits. Emphasized is the need to identify high potential from underserved populations for gifted education services.